Scientific profile and professional responsibility of Court-appointed Medical Technical Consultants in Italy: time for a specific educational curriculum? - Conti, Andrea Alberto (Acta Biomedica Atenei Parmensis, 2014)
Court-appointed Technical Consultants (CTCs) are fundamental figures in the Italian judicial system. CTCs are experts appointed by judges in order to supplement their activities by ascertaining, collecting and analyzing facts concerning the specific subject of a lawsuit. These experts formulate opinions, gather motivations and perform checks to provide clear, objective and irrefutable answers to the questions posed by judges. With direct reference to the medical field, while police doctors (specialists in forensic medicine) follow an academic, dedicated, well-structured educational curriculum, the University specialty school in Forensic Medicine, other medical CTCs, though not infrequently luminaries with one or many medical specialties and professional acknowledgments, may have no specific legal-medicine and juridical expertise, precisely because a similar expertise is not formally required of them. In the light of these considerations, in Italy some professionals of the legal world, and of the health context too, have proposed for medical CTCs targeted educational pathways, which would provide these experts with formal specific qualifications. In synthesis and in conclusion, a full knowledge and a rigorous respect of the rules of legal proceedings emerge as increasingly important characteristics for current and future Court-appointed Technical Consultants, together with a specific educational curriculum.